Artificial Intelligence and Computational Intelligence Third International Conference, AICI 2011, Taiyuan, China, September 24-25, 2011, Proceedings, Part I - Deng, Hepu.; Miao, Duoqian; Lei, Jingsheng; Wang, Fu Lee.; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This three-volume proceedings contains revised selected papers from the Second International Conference on Artificial Intelligence and Computational Intelligence, AICI 2011, held in Taiyuan, China, in September 2011. The total of 265 high-quality papers presented were carefully reviewed and selected from 1073 submissions. The topics of Part I covered are: applications of artificial intelligence; applications of computational intelligence; automated problem solving; biomedical inforamtics and computation; brain models/cognitive science; data mining and knowledge discovering; distributed AI and agents; evolutionary programming; expert and decision support systems; fuzzy computation; fuzzy logic and soft computing; and genetic algorithms.
Electronic reproduction.
Keywords: Computer science; Software engineering; Computer software; Information storage and retrieval systems; Artificial intelligence; Electronic books